The association between sleep duration and prostate cancer: A systematic review and meta-analysis. Issue 28 (10th July 2020) - Liu, Ranlu; Wu, Shangrong; Zhang, Baoling; Guo, Mingyu; Zhang, Yang
Abstract : Abstract: The association between sleep duration and prostate cancer (PCa) risk is still unclear. We performed a systematic review and meta-analysis to explore if sleep duration is associated with PCa in men. A comprehensive literature search was conducted in November 2019 based on the Pubmed, Embase, and Cochrane databases. After extracting the data, the random effects model was used to calculate the pooled Risk Ratio (RR) and it's 95% confidence interval (CI) to represent the correlation between sleep duration and PCa risk. Overall, we included 6 studies in our meta-analysis. Our pooled results showed that neither short sleep (RR = 0.99; 95%CI:0.91-1.07, P = .74) nor long sleep (RR = 0.88; 95%CI:0.75-1.04, P = .15) was associated with the risk of PCa. Sleep duration has no significant effect on PCa risk. Long sleep may have a potential protective effect on PCa incidence.